Analysis on genetic diversity of 51 Grape germplasm resources - Qingchun Yue; Chenfei Zhang; Qinghao Wang; Wenjing Wang; Jinyang Wang; Yueyan Wu (Ciência Rural, 2019)
ABSTRACT: The objective of this study is to research the genetic diversity of the ‘ Zuijinxiang ’ grape and its mutant breeding F1 plants, we screened the excellent mutant plants with potential breeding value. 50 mutated single plants obtained from 137Cs-γ irradiated ‘Zuijinxiang’ grape seeds were used as research objects, and SCoT molecular marker technology was used for genetic diversity and variation analysis, and clustering research was carried out. The results showed that: (1) 36 SCoT primers produced abundant polymorphisms, and the amplification results showed obvious bright bands, and the amplification efficiency and polymorphism rate were 100%. (2) A total of 221 bands were amplified by 36 primers, of which 175 were rich in polymorphism, the average polymorphic percentage was 80.3%, and the average genetic similarity coefficient was 0.916. (3) The number of observed alleles (Na) ranged from 4 to 8, with an average of 6.1389; the number of effective alleles (Ne) ranged from 1.2772 to 5.6322 with an average of 3.5968; the desired heterozygosity (He) The range is from 0.2192 to 0.8344, the average is 0.6965; the observed heterozygosity (Ho) ranges from 0.1656 to 0.7808 with an average of 0.3035; the Nei’s gene diversity index (H) ranges from 0.2170 to 0.8224 with an average of 0.6863; Shannon-Wiener The index (I) ranges from 0.5186 to 1.8597 with an average of 1.4517. (4) UPGMA clustering of 51 materials showed that the test materials could be divided into three groups when the genetic distance was 0.856. The experiment shows that the genetic diversity of the ‘Zuijinxiang’ radiation variation germplasm resources is rich. In addition, SCoT molecular marker technology can distinguish the materials with close genetic distance, and can be used for early identification techniques of grape mutant materials. This study provides a theoretical basis for the development of excellent mutant germplasm of ‘Zuijinxiang’ grapes.